The Rhyacophila fasciata Species Complex (Trichoptera: Rhyacophilidae) in Turkey with description of a new species, Rhyacophila anatolica Ekingen & Valladolid, sp. nov., based on morphological, genetic, and ecological evidence - Valladolid, Maria; Ekingen, Pinar; Arauzo, Mercedes; Dorda, Beatriz A.; Rey, Isabel (Zootaxa, 2024)
The morphology of the larva, pupa, male, and female of Rhyacophila anatolica Ekingen & Valladolid, sp. nov., from Turkey is described. We also present molecular mtCOI data, and compare sequences of R. anatolica with corresponding data from R. fasciata Hagen 1859, as well as with other species in the “R. fasciata Species Complex”: R. septentrionis McLachlan 1865, R. denticulata McLachlan 1879, R. sociata Navás 1916, R. kykladica Malicky & Sipahiler 1993, R. delici Kučinić & Valladolid 2020, R. viteceki Valladolid & Kučinić 2020, R. macedonica Karaouzas, Valladolid & Ibrahimi 2022, and R. loeffleri Valladolid & Waringer 2023. Our study revealed morphological differences between R. fasciata and R. anatolica, as well as genetic differences among the other taxa of the “R. fasciata Species Complex,” supporting the recognition of R. anatolica as a new species.